The Concept of 21st-Century Inclusive Education from a Hadith Perspective - Junaris, Imam; Firmansyah, Iwan (Journal of Development Research, 2026)
21st-century education requires an inclusive and adaptive learning system that recognizes and accommodates student diversity. In this context, Islamic values derived from Hadith provide a normative foundation for developing just and humanistic education. This study aims to examine the concept of inclusive education from a Hadith perspective and to analyze its relevance to contemporary educational needs. A qualitative library-based research method was employed, utilizing primary sources from major Hadith compilations and secondary sources related to Islamic and inclusive education. Data were analyzed using a thematic and interpretative approach to identify key principles and their educational implications. The findings reveal that Hadith narrations emphasizing equality, compassion (rahmah), the obligation to seek knowledge, and respect for human dignity are closely aligned with the core principles of 21st-century inclusive education. However, the study also identifies a gap between these normative values and their practical implementation in modern educational contexts. Therefore, the integration of Hadith-based values requires systematic operationalization through inclusive curriculum design, differentiated instructional strategies, and the development of supportive school cultures. This study contributes by offering a conceptual framework that integrates Islamic ethical principles with contemporary inclusive education models. It argues that the Hadith perspective not only provides moral and spiritual guidance but also has practical relevance when translated into structured educational practices. Thus, inclusive education based on Hadith can serve as a transformative approach that is both contextually relevant and aligned with Islamic values.